An Experience of Atypical Mycobacterial Postoperative Infection in a Tertiary Hospital - Haque, Quazi Manjurul (KYAMC Journal, 2022)
Abstract not available KYAMC Journal Vol. 13, No. 02, July 2022: 61-62